2017
DOI: 10.1039/c7ra03387g
|View full text |Cite
|
Sign up to set email alerts
|

A review of Mn-containing oxide catalysts for low temperature selective catalytic reduction of NOx with NH3: reaction mechanism and catalyst deactivation

Abstract: The reactions over Mn-containing selective catalytic reduction (SCR) catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 171 publications
(201 reference statements)
3
75
0
Order By: Relevance
“…Thus, the NO reduction is dominated by reaction (2) and not reaction (3) in the temperature range of 100 C to 160 C. In fact, the Gibbs free energy for reaction (2) (DG 0 298 ¼ À1651 kJ mol À1 ) is far below that of reaction (1) (DG 0 298 ¼ À70 kJ mol À1 ). 15 In addition, reaction (3) is limited by reaction (1). Therefore, it can be concluded that the reduction of NO was dominated by reaction (2) in the investigated temperature range.…”
Section: Mechanism Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the NO reduction is dominated by reaction (2) and not reaction (3) in the temperature range of 100 C to 160 C. In fact, the Gibbs free energy for reaction (2) (DG 0 298 ¼ À1651 kJ mol À1 ) is far below that of reaction (1) (DG 0 298 ¼ À70 kJ mol À1 ). 15 In addition, reaction (3) is limited by reaction (1). Therefore, it can be concluded that the reduction of NO was dominated by reaction (2) in the investigated temperature range.…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…13) and Mn/Ce-ZrO 2 , 14 show a relatively high activity at low temperature. 15 Moreover, Mn could improve the performance of V 2 O 5 /TiO 2 catalyst. 16 However, most of previous work placed emphasis on the NO conversion.…”
Section: -11mentioning
confidence: 99%
“…In the recent past, we published a series of papers on Mn-based SCR catalysts that showed a highly promising deNO x potential in the low-temperature region [5,[22][23][24][25][26]. However, these catalysts are very sensitive to the presence of SO 2 in the feed and exhibit lower N 2 selectivity [8,[27][28][29]. Hence, the development of catalysts that show both good low-temperature activity and high SO 2 /H 2 O durability is of great importance for the NH 3 -SCR reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The DRIFTS observation over unmodified Fe 2 O 3 can be incorporated into a catalytic cycle (with undesirable pathway being listed in Figure S8) based on L NH3 active species according to an Eley‐Rideal mechanism . Figure S8 illustrates the activation of adsorbed NH 3 as well as the occurrence of undesirable side reaction, in which some activated NH 3 are consumed by reaction with surface NO 3 − species . The formation of NO 3 − species and N 2 O by‐product was confirmed by DRIFTS and N 2 selectivity analysis, respectively, over the Fe 2 O 3 as shown in Figure S3 and Figure b.…”
Section: Resultsmentioning
confidence: 99%